Kekerasan dalam Pacaran: Anatomi Konflik dan Penyelesaiannya - Nugroho, Wahyu Budi; Sushanti, Sukma (Fakultas Ilmu Sosial dan Ilmu Politik UIN Walisongo Semarang, 2019)
This article aims to study one of the social relationship forms called â€œlove relationshipâ€. Love relationships may define as a relation between two individuals, opposite sex generally, in addition, to adapt to each other before marriage. As one of the social relationship forms, it can not avoid conflict, even violence. Those concerns are becoming the focus study in this research. Furthermore, this research using the individual's conflict theory by George Simmel, conflict theory of Lewis A. Coser, and also existential sociology of Jean-Paul Sartre about love. The method of this research is qualitative which explanative-descriptive research variant. Based on the research, it is found that most of the informants lie love relationship in â€œfunctionalâ€ form. Despite this, most of them are not realized of love relationship violence which held. Finally, the resolution of all matters took moderate to radical form, it is reconciliation or broke up, and even not engaged anymore.Â Â